2014
DOI: 10.1016/j.neuron.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

A Whole-Brain Atlas of Inputs to Serotonergic Neurons of the Dorsal and Median Raphe Nuclei

Abstract: The serotonin system is proposed to regulate physiology and behavior and to underlie mood disorders; nevertheless, the circuitry controlling serotonergic neurons remains uncharacterized. We therefore generated a comprehensive whole-brain atlas defining the monosynaptic inputs onto forebrain-projecting serotonergic neurons of dorsal versus median raphe based on a genetically restricted transsynaptic retrograde tracing strategy. We identified discrete inputs onto serotonergic neurons from forebrain and brainstem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
261
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 394 publications
(279 citation statements)
references
References 81 publications
15
261
1
2
Order By: Relevance
“…Whole-brain mapping of monosynaptic connectivity using modified rabies viruses can generate large datasets of cell-type-specific connectomes at the mesoscale level 2931 . We applied rabies virus tracing to identify the presynaptic partners of defined neuronal subtypes in the corticostriatal pathway (Supplementary Video 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole-brain mapping of monosynaptic connectivity using modified rabies viruses can generate large datasets of cell-type-specific connectomes at the mesoscale level 2931 . We applied rabies virus tracing to identify the presynaptic partners of defined neuronal subtypes in the corticostriatal pathway (Supplementary Video 2).…”
Section: Resultsmentioning
confidence: 99%
“…No statistical methods were used to pre-determine sample sizes but our sample sizes are similar to those reported in previous publications 30,31 . Injections considered outside of the stereotactic coordinates were excluded and not further imaged or processed.…”
Section: Methodsmentioning
confidence: 95%
“…Monosynaptic viral tracing of neuromodulatory systems has been used in the noradrenergic, dopaminergic and serotonergic systems (Beier et al, 2015; Faget et al, 2016; Lerner et al, 2015; Ogawa et al, 2014; Pollak Dorocic et al, 2014; Schwarz et al, 2015; Watabe-Uchida et al, 2012; Weissbourd et al, 2014). BFc monosynaptic tracing was also reported (Do et al, 2016; Hu et al, 2016) though without reference to target specificity.…”
Section: Discussionmentioning
confidence: 99%
“…The cluster of the labeled neurons is likely to be the zebrafish homolog of the habenular-projecting globus pallidus (GPh) neurons in lamprey and the habenular-projecting entopeduncular nucleus (EPh) neurons in mouse (Shabel et al, 2012;Stephenson-Jones et al, 2013). Recently, it has been shown that the mouse LHb has the direct glutamatergic projection to the MR as the zebrafish vHb does (Pollak Dorocic et al, 2014). Thus, the vEP in zebrafish or EPh in mouse (vEP/ EPh), vHb in zebrafish or LHb in mammals (vHb/LHb), and MR constitutes a neural pathway that is conserved throughout vertebrate evolution, and the neural activity conducted through this pathway may act as a neural substrate for representation of negative reward expectation value in CS-associated environments.…”
Section: Discussionmentioning
confidence: 99%